THE INTEGRATION OF ARTIFICIAL INTELLIGENCE (AI) IN SECOND LANGUAGE ACQUISITION - Leli Ridayani; Wahyudi Badri; Dian Susyla (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Second Language Acquisition (SLA) has undergone significant transformation alongside technological advancements, particularly through the integration of Artificial Intelligence (AI). AI technology holds great potential for enhancing the efficiency of language learning while introducing more adaptive and personalized methods. By leveraging AI, learners can experience more interactive learning environments, enabling them to practice language skills in ways that are simultaneously enjoyable and challenging. AI also provides flexible and personalized learning tools, allowing teaching materials to be tailored to individual skill levels, learning styles, and paces. This technology fosters a dynamic learning experience by offering instant feedback, helping learners correct their mistakes more quickly. Moreover, AI-based applications and platforms, such as chatbots and simulations, enhance immersion in language learning, enabling learners to engage in authentic real-life scenarios. Moving forward, AI is expected to become increasingly integrated into language education, offering even more opportunities to support the success of second language learning worldwide.